Genomic deletions on 16p11.2 associated with severe obesity in Brazil - da Silva Assis, Izadora Sthephanie; Salum, Kaio Cezar Rodrigues; Felício, Rafaela de Freitas Martins; Palhinha, Lohanna; de Medeiros Abreu, Gabriella; Silva, Tamara; Mattos, Fernanda Cristina Carvalho; Rosado, Eliane Lopes; Zembrzuski, Verônica Marques; Campos Junior, Mario; Maya-Monteiro, Clarissa Menezes; Cabello, Pedro Hernán; et al. (Frontiers in Endocrinology, 2025)
Introduction Genetic obesity is considered a rare disease, affecting up to 10% of patients with severe early-onset obesity. Over the past years, significant advances have been made; however, the majority of patients are misdiagnosed with polygenic obesity. Thus, this study aimed to identify deleterious copy number variations (CNVs) linked to obesity and explore the clinical phenotypes. Method The sample comprised 195 adults with severe obesity (BMI≥35kg/m2) who developed this phenotype during childhood or adolescence. We investigated the CNV using Multiplex Ligation-dependent Probe Amplification [MLPA] and real-time PCR. Chromosomal microarray analysis was used to assess the extent of genomic alterations. Results One patient showed a ~206 kb deletion in the distal of the 16p11.2 region, encompassing twelve genes. The gene linked to the development of severe obesity was SH2B1. This alteration was found in a male patient with metabolic syndrome (MS), and hypertension. Two patients exhibited a large deletion in the proximal of the 16p11.2 region. One patient showed a ~534 kb deletion without twenty-nine genes. This female patient had hypertension and bronchitis. The other patient presented a ~598 kb deletion of the proximal 16p11.2 region, including thirty-two genes. This female patient exhibited MS, and moderate binge-eating disorder. Conclusion Our study showed three genomic deletions at the 16p11.2 region in patients with severe obesity from Brazil. These results support the clinical utility of genetic testing to identify patients with the genetic form of obesity who may benefit from specific medical treatment, family genetic counseling, and targeted therapeutic intervention.